Efficacy and Safety of Auricular Acupuncture for Cognitive Impairment and Dementia: A Systematic Review. (31st May 2018) - Kwon, Chan-Young; Lee, Boram; Suh, Hyo-Weon; Chung, Sun-Yong; Kim, Jong Woo
Abstract : Objectives . To analyze the efficacy and safety of auricular acupuncture (AA) in patients with cognitive impairment and dementia. Methods . Twelve electronic databases were searched for randomized controlled trials evaluating effects of AA in patients with cognitive impairment and/or dementia, from their inception to August 2017. The primary outcome was cognitive function, and secondary outcomes were self-care ability, quality of life, clinical efficacy rate, and incidences of adverse events. Results . Nine studies were included, and five involving 677 participants were analyzed quantitatively. Compared with Western medications (WM), AA had mixed effects on cognitive functions (Mini-Mental State Examination [MMSE], mean difference [MD] 0.73, 95% confidence interval [CI] −0.02 to 1.48; Hierarchic Dementia Scale [HDS], MD 2.21, 95% CI 1.09 to 3.33); there was no significant improvement in the activities of daily living (ADL) score (MD 0.20, 95% CI −3.51 to 3.91) in patients with vascular dementia (VD). Compared to WM, AA combined with WM showed better clinical efficacy rate (risk ratio [RR] 1.42, 95% CI 1.06 to 1.91) in patients with VD; there was no significant improvement in cognitive functions (MMSE, MD 0.97, 95% CI −0.44 to 2.38; Montreal Cognitive Assessment [MoCA], MD 0.22, 95% CI −1.83 to 2.27) in patients with mild cognitive impairment (MCI). Compared to herbal medicine (HM), AA plus HM showed significant improvements in cognitive function (MMSE, MD 1.31, 95% CI 0.13 to 2.49) in patients with MCI and patients with vascular cognitive impairment, no dementia (VCIND) and in ADL score (MD −6.70, 95% CI −8.78 to −4.62) in patients with MCI. No adverse event associated with AA was reported. Conclusion . The evidence reveals mixed efficacy of AA in patients with cognitive impairment and/or dementia. However, the results were inconclusive because of the small number and poor methodological quality of the included studies.